Right hemisphere engagement in language abilities in older adults: indication of compensation rather than decline - Solomons, Daniel; Rodriguez-Fernandez, Maria; Mery-Muñoz, Francisco; Arraño-Carrasco, Leonardo; Toloza-Ramirez, David; Sahli-Costabal, Francisco; Mendez-Orellana, Carolina (Frontiers in Aging, 2025)
IntroductionStructural brain changes during aging have been used as specific markers to distinguish normal aging from dementia. Changes in specific cognitive abilities such as episodic memory, processing speed, and executive functions, are observed in healthy aging. Limited evidence reports changes in linguistic functions alongside structural and functional brain changes. This study investigates correlations between language performance, gray matter volume (GMV), and neural activity in language regions, adjusted for demographic factors, in healthy older adults.MethodsTwenty-seven right-handed participants aged 60–87 were evaluated for overall linguistic performance using the Spanish version of ScreeLing (SCL) test and phonemic fluency and semantic verbal fluency tasks (PF and SF). Participants also underwent an MRI session during which they performed a functional MRI language task. T1-weighted MRI scans were used to measure GMV in specific language-related regions and assess language lateralization. Correlational analyses were conducted between language scores, GMV, years of education, age, sex, and fMRI lateralization.ResultsIn the right hemisphere (RH), significant positive correlations were found between SCL scores and GMV in the orbital inferior frontal gyrus (r = 0.5402; p = 0.0044) and the superior temporal gyrus (r = 0.516; p = 0.007). Furthermore, SCL and Phonemic fluency positively correlated with years of education, indicating that higher education enhances speech performance. No significant correlations were found in the left hemisphere (LH). Age, sex, and fMRI lateralization did not significantly correlate with specific linguistic scores.DiscussionThese results challenge the current view of the role of the right hemisphere in language performance as increased GMV in specific right hemisphere language regions is associated with better language performance, highlighting the role of the right hemisphere in supporting language skills during healthy aging.